ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PENDAPATAN ASLI DAERAH PROVINSI KALIMANTAN BARAT TAHUN 2001-2010 - Fara Dina (Jurnal Khatulistiwa Informatika, 2013)
Efforts to increase revenue Local Government Original Receipt can be done by increasing the effectiveness of the collection, by optimizing the potential that exists and will continue to be exploring new revenue sources that allow it to be in potential tax collection or levy. This study aims to analyze the effect of government contribution of third party, Investment income the value of the vehicle and West Kalimantan Province. This research use secondary data (eries times) of year 2001 to 2010. To achieve the research objectives were used regression analysis model and followed by statistical and econometric testing. Result estimates of third party variable showing the negative effect, that mean if increment total contribution of third party occur will bring on contribution of third party reduction as big as 0,03. Should this variable have positive effect. But variables such third party contributions have a significant effect to local goverment original receipt. Regression estimation result indicate that the variable two-wheeled vehicles or more, have a positive effect but not significant effect on PAD. It means if there is an increase the number of two-wheeled vehicles or more, as much as one rupiah of revenue will decrease by 63,25 rupiah. Regression estimation result indicate that the variable four-wheeled vehicles or more, have a positive effect and significant effect on PAD. It means if there is an increase the number of four-wheeled vehicles or more, as much as one rupiah of revenue will increase by 6.952 rupiah. The estimation of regional investment variable shows a positive and significant influence if means increase in the amount of investment in the region will increase revenue by 42,66 rupiah.Key words : Local Goverment Original Receipt of West Kalimantan Province